Who should benefit from free movement? A comparative study on British and Romanian political discourses in the pre-Brexit period - Heinikoski Saila (The Finnish Centre for Romanian Studies (FICROS), 2022)
The right to free movement in the European Union is currently an extremely topical matter, accentuated by the Brexit referendum, and its eventual impacts on the free movement regime. In this article, I analyse how the British Prime Ministers and the Home Secretaries as well as the Romanian Presidents and the Prime Ministers between January 2005 and January 2015 discussed the right to free movement in terms of the benefits and costs it incurs. British statements were collected from the government and party websites, and Romanian statements were collected from the official website of the President of Romania, from the Prime Minister’s website as well from the archives of the Romanian government. The analysis reveals that the right to free movement was discussed in the British and the Romanian contexts mainly in connection with social security and brain drain, respectively. The article is divided in two parts, first of which considers theoretical and methodological questions, and the second discusses utility-related utterances about free movement in their political contexts. Finally, I draw my conclusions relying on the sections concerning utility-based questions related to free movement in the British and the Romanian discourses. I argue that the British approach relied on the view that only UK citizens should be entitled to social benefits. Romanian politicians, in turn, balanced between brain drain and benefits for individual citizens. Despite the seemingly different approaches, both perspectives were informed by the view that free movement should benefit societies, or rather, that people should not be a strain on the society. Both also represented free movement as a zero-sum game where one’s gain is another’s loss, and surprisingly, the national economy in both countries was presented as losing in the game.